2012
DOI: 10.1038/leu.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Gfi-1 inhibits proliferation and colony formation of p210BCR/ABL-expressing cells via transcriptional repression of STAT 5 and Mcl-1

Abstract: Expression of the transcription repressor Gfi-1 is required for the maintenance of murine hematopoietic stem cells. In human cells, ectopic expression of Gfi-1 inhibits and RNA interference-mediated Gfi-1 downregulation enhances proliferation and colony formation of p210BCR/ABL expressing cells. To investigate the molecular mechanisms that may explain the effects of perturbing Gfi-1 expression in human cells, Gfi-1-regulated genes were identified by microarray analysis in K562 cells expressing the tamoxifen-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…STAT5 is a critical participant in TKI resistance 11,12 and the clinically available dopamine reuptake inhibitor pimozide has been demonstrated to inhibit STAT5 activation in CML cells, subsequently enhancing TKI-induced apoptosis. 3,15 We establish that treatment with STAT5i, which targets the SH2 domain of STAT5, 36 had little effect as a sole agent in cell lines or primary CP-CML CD34 þ cells. Inhibition of STAT5 with pimozide or STAT5i in combination with only 30 min exposure to TKI, induced death in both BCR-ABL1 þ cell lines and primitive CP-CML CD34 þ cells despite complete removal of dasatinib or imatinib after.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…STAT5 is a critical participant in TKI resistance 11,12 and the clinically available dopamine reuptake inhibitor pimozide has been demonstrated to inhibit STAT5 activation in CML cells, subsequently enhancing TKI-induced apoptosis. 3,15 We establish that treatment with STAT5i, which targets the SH2 domain of STAT5, 36 had little effect as a sole agent in cell lines or primary CP-CML CD34 þ cells. Inhibition of STAT5 with pimozide or STAT5i in combination with only 30 min exposure to TKI, induced death in both BCR-ABL1 þ cell lines and primitive CP-CML CD34 þ cells despite complete removal of dasatinib or imatinib after.…”
Section: Discussionmentioning
confidence: 98%
“…1 The signal transducer and activator of transcription 5 (STAT5) is constitutively active in CML cells as a result of Bcr-Abl activation. 2 In addition, the STAT5 transcriptional repressor Gfi-1 is down regulated in CML, 3 and we have previously demonstrated that low levels of GFI-1 at diagnosis predict progression to blast crisis. 4 Conventionally, STAT5 activation occurs in response to cytokine signaling through JAK kinases.…”
Section: Introductionmentioning
confidence: 96%
“…BCR-ABL is a tyrosine kinase responsible for malignant transformation by activating multiple signal pathways, including the PI3K/Akt, MAPK/ERK and STATs (2)(3)(4), leading to aberrant cell survival (5,6). The successful introduction of the tyrosine kinase inhibitors (TKIs), constitutes an effective strategy in CML.…”
Section: Introductionmentioning
confidence: 99%
“…35 That study, along with their previous work, 36 demonstrated the biological importance of the GFI1/STAT5B/Mcl-1 regulatory pathway on proliferation and survival of CML cells. In a study of CP-CML patients, Kok et al demonstrated that decreased GFI1 expression at diagnosis is highly correlative with disease progression and transformation to BC.…”
Section: Gfi-1mentioning
confidence: 87%